2009
DOI: 10.1111/j.1600-0897.2009.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Endometrial Osteopontin mRNA Expression and Plasma Osteopontin Levels are Increased in Patients with Endometriosis

Abstract: Osteopontin may be involved in the pathogenesis of endometriosis and plasma OPN may be a useful non-invasive marker for the diagnosis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
4
31
0
1
Order By: Relevance
“…Our findings on OPN gene expression are in agreement with other reports which have demonstrated an increase in OPN expression in a rat model of endometriosis in comparison to normal rats endometrial tissue and in patients with endometriosis in comparison with control subjects (28, 51-53). According to the functional role of OPN in cell adhesion, migration, differentiation and invasion of tumor cells, it could be assumed that OPN enhance endometrial invasiveness, proliferation and survival in ectopic lesions in animal models.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings on OPN gene expression are in agreement with other reports which have demonstrated an increase in OPN expression in a rat model of endometriosis in comparison to normal rats endometrial tissue and in patients with endometriosis in comparison with control subjects (28, 51-53). According to the functional role of OPN in cell adhesion, migration, differentiation and invasion of tumor cells, it could be assumed that OPN enhance endometrial invasiveness, proliferation and survival in ectopic lesions in animal models.…”
Section: Discussionsupporting
confidence: 93%
“…Another study by the same group showed lower levels of osteopontin RNA messenger (mRNA) in women with moderate to severe endometriosis during the early secretory phase (Burney et al, 2007). On the other hand, Cho et al (2009) showed that higher osteopontin mRNA was expressed in the eutopic endometrium and in the plasma of women with endometriosis when compared to controls. However, the authors of these studies included fertile and infertile patients with endometriosis and during different periods of the cycle, precluding the comparison of their results with those found by Casals et al (2012) and those presented here.…”
Section: Discussionmentioning
confidence: 95%
“…In this context, the literature presents conflicting studies evaluating progesterone receptors (Attia et al, 2000;Igarashi et al, 2005;Shen et al, 2015), αvβ3 integrin (Ordi et al, 2003;Wei et al, 2009;Casals et al, 2012) and osteopontin (Burney et al, 2007;Cho et al, 2009;Wei et al, 2009;Casals et al, 2012) in the eutopic endometrium of women with endometriosis, especially with respect to disease-associated infertility. Moreover, to date, there is no study evaluating the expression of HB-EGF in these patients and no previous study simultaneously evaluated the expression of these five genes in infertile patients with endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al in 2009 found no difference OPN expression in the eutopic endometrium of women with endometriosis during the mid-secretory phase [22]. Interestingly, in the same year, Cho et al found significantly increased OPN mRNA levels in eutopic endometrium of women with endometriosis [27].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 90%